Translation of Chinese xiehouyu (sayings) and relevance theory - Liu, C.; Zhang, Grace (Akadmiai Kiad, 2006)
This paper investigates how the phenomenon of fuzzy language, such as 'many' in 'Mary has many friends', can be explained by Relevance Theory (RT, Sperber and Wilson, 1986, 1995, 1998, 2002, Wilson and Sperber 2002). It is concluded that the use of fuzzy language conforms with optimal relevance in that it can achieve the greatest positive effect with the least processing effort. It is the communicators themselves who decide whether or not optimal relevance is achieved, rather than the language form (fuzzy or non-fuzzy) used. People can skillfully adjust the deployment of different language forms or choose appropriate interpretations to suit different situations and their communication needs. However, there are two challenges to RT: a. to extend its theory from individual relevance to group relevance; b. to embrace cultural considerations (because when relevance principles and cultural protocols are in conflict, the latter tends to prevail).